2019
DOI: 10.1038/s41598-019-46985-0
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based radiomics signature is a quantitative prognostic biomarker for nasopharyngeal carcinoma

Abstract: This study aimed to develop prognosis signatures through a radiomics analysis for patients with nasopharyngeal carcinoma (NPC) by their pretreatment diagnosis magnetic resonance imaging (MRI). A total of 208 radiomics features were extracted for each patient from a database of 303 patients. The patients were split into the training and validation cohorts according to their pretreatment diagnosis date. The radiomics feature analysis consisted of cluster analysis and prognosis model analysis for disease free-sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 41 publications
4
43
1
Order By: Relevance
“…The combined signature was the one with the best performance. This is in line with the majority of studies of literature on radiomics applications to head and neck cancer (see [ 10 , 18 ] or the training set in [ 13 ]).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The combined signature was the one with the best performance. This is in line with the majority of studies of literature on radiomics applications to head and neck cancer (see [ 10 , 18 ] or the training set in [ 13 ]).…”
Section: Discussionsupporting
confidence: 85%
“…In terms of DFS, the combined radiomic-clinical model (HR 1.98 (1.03–3.80), log-rank p = 0.037) was the only one determining a significant split in the Kaplan-Meier curves between low- and high-risk patients. However, The C-index of the combined model in the study was lower than that reported by the previous studies on NPC [ 10 , 12 , 16 ]. This may depend on the fact that those models were trained specifically for DFS prognosis.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…At the time, CT radiomics research in HNC concentrated on the latter category ( 14 ). Discovered through our search strategy, abstracts from conference proceedings (Table S3 in Supplementary Material) all focused on prognostic endpoints in NPC patients ( 71 – 73 ). Thus, perhaps, MRI radiomic studies in HNC are trending toward these outcome measures.…”
Section: Discussionmentioning
confidence: 99%